2007
DOI: 10.1063/1.2403970
|View full text |Cite
|
Sign up to set email alerts
|

Conductivity profile determination by eddy current for shot-peened superalloy surfaces toward residual stress assessment

Abstract: This paper demonstrates a swept high frequency eddy current (SHFEC) methodology that can determine near-surface conductivity deviation profiles of shot-peened superalloy surfaces, from which residual stress state can be assessed nondestructively. Our methodology is built around a laboratory-grade SHFEC hardware and a model-based SHFEC data inversion software, both described in this article. For the demonstration, a series of shot-peened Inconel 718 block specimens is prepared and examined by the proposed SHFEC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…Eddy current (EC) method has been studied regarding its potential for measuring subsurface and surface residual stress based on the empirical piezoresistivity effect [2][3][4][5][6]. It has been reported that shot peening-induced change in conductivity measured using the EC method is affected by the microstructure of the material [5,[7][8].The objective of this study is to understand how the microstructure of the samples affect the eddy current measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Eddy current (EC) method has been studied regarding its potential for measuring subsurface and surface residual stress based on the empirical piezoresistivity effect [2][3][4][5][6]. It has been reported that shot peening-induced change in conductivity measured using the EC method is affected by the microstructure of the material [5,[7][8].The objective of this study is to understand how the microstructure of the samples affect the eddy current measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Using this method, the authors previously showed that the electromagnetic properties of the surface of alloy tool steel, Japanese Industrial Standard (JIS) SKD61, peened by CP varied with processing time [10]. Also using this method, the electrical conductivity in shot-peened nickel-base superalloys was found to vary [8,9]. Blodgett and Nagy used an eddy current method to show that the electrical conductivity varied with axial stress [5].…”
Section: Introductionmentioning
confidence: 93%
“…There are a number of methods that use electromagnetic properties to evaluate the residual stress in the surface layers of metallic components, such as the potential drop technique [6], the Barkhausen method [7], and the eddy current method [5,8,9]. In the present paper, we examine the eddy current method in order to establish a rapid nondestructive test for measuring stress in the surface layers of various metallic materials, including paramagnetic and ferromagnetic materials.…”
Section: Introductionmentioning
confidence: 98%
“…It is observed in the present study that increase or decrease in electrical conductivity can be under predicted, if material isotropy is assumed. Shen et al (2007) observed that anomalous negative conductivity changes in the near surface region in shot peened nickel alloys is due to, among other factors, anisotropic deformation of the stressed material. Morozov et al (2010) investigated anisotropic in-plane longitudinal and transverse electrical conductivity inversion for −2% variations using directional probes.…”
Section: Introductionmentioning
confidence: 96%